Growth and instability in area, production and yield of pulses in Punjab - Singh, Lovepreet and Bansal, Surbhi (Agriculture Situation In India)
Punjab is the highest contributor in the cultivation of wheat and paddy but it lags behind in cultivation of pulses. The production of pulses is declining and its variability has increased in the past four decades. The present study is an attempt to examine the pattern of growth and instability in area, production and productivity of pulses in Punjab. The time series data for the period 1985-86 to 2017-2018 regarding area, production and yield of pigeon peas, urad bean, peas, mung bean, chickpea, lentil as well as total pulses as a whole has been used to compute compound growth rates, coefficient of variation, Cuddy-Della Valle Index (CDI) and Coppock$1 (Bs Instability Index (CII) to attain the objectives of the study. The growth rate of area and production of total pulses showed a decline of 6.17 and 5.60 percent per annum, respectively, but showed positive significant change in productivity, i.e., 0.61 percent per annum for pulses during the study period. The declining growth rate of area and production may be due to dominant wheat and paddy monoculture, mechanized farming (which leads to more production of other profitable crops) and the risk associated with pulses in terms of yield and profitability also leads to replacement of area under pulses. Mung bean is the major grown crop in Punjab as it constituted about 71 percent of area and 68 percent of total pulses production during TE 2017-18. The results of instability shows that almost all the pulses observed more variation in the production and least in the productivity. It is suggested that there is a need to strengthen research and development (R&D) for improving productivity of pulses in state. More focus should be given to the summer crops like mung bean which emerged as a good source of income to the farmers. s
Keywords: Punjab, Pulses, CDI, CII, growth, Instability